Surface Area Evaluation of Cartesian Mirrors with Varying Asphericity Factor - Yaseen, Nour Mohammedhasan (Al-Nahrain Journal of Science, 2018)
The dependence of a surface depth and a surface area on the asphericity factor of Cartesian surfaces is exhibited. This has been achieved by evaluating the surface areas of Cartesian surfaces with constant radius of curvature and constant aperture diameter and varying asphericity factor. For this purpose a skew ray-tracing code is constructed and a surface area program in MATLAB, for computing the areas, is composed. The evaluation of these areas demanded modifying the equation that describes these surfaces. The modification is summarized by converting the surface equation into a curve equation and the latter is employed to evaluate the areas by making use of a ray-tracing and MATLAB.